Facilitated magnesium atom adsorption and surface diffusion kinetics via artificial bismuth-based interphases. Issue 74 (25th August 2021) - Chu, Honghao; Zhang, Zhonghua; Song, Zihao; Du, Aobing; Dong, Shanmu; Li, Guicun; Cui, Guanglei
Abstract : Bismuth-based artificial interphases facilitate magnesium atom adsorption and fast surface diffusion, dramatically improving the magnesium stripping/plating kinetics for rechargeable magnesium batteries. Abstract : Robust bismuth-based interphases, comprised of bismuth and bismuth oxides, were developed using galvanic replacement reactions. Facilitated Mg atom adsorption and distinct interfacial Mg atom migration were demonstrated, greatly lowering the electrochemical energy penalty (23 mV for the nucleation process and 69 mV for the growth process at 1.0 mA cm −2 ).